ANALISIS DAN PERANCANGAN SISTEM INFORMASI DENGAN INTRANET: STUDI KASUS PERSEDIAAN MATERIAL PT BALFOUR BEATTY SAKTI INDONESIA - Darudiato, Suparto; Punta, Krisma (CommIT (Communication and Information Technology) Journal, 2007)
Article discuss problem faced by PT Balfour Beatty Sakti Indonesia (PT BBSI), which is lack planning ofmaterial inventory supply. Inventory was bought overly as safety stock. That caused inventory stacking so the companyoperation less efficient and caused damage on the material itself. The inventory model will be used to overcome theproblem is Periodic Order Quantity (POQ) model that was develop from Economic Order Quantity (EOQ) basic model.The proposed problem solution will be applied in inventory information system in form of analysis and design of materialinventory information system object oriented using Mathiassen approach.Keywords: information system, inventory, intranet, material